2017
DOI: 10.1126/sciadv.1701735
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and near-complete dissolution of wood lignin at ≤80°C by a recyclable acid hydrotrope

Abstract: We report a near-complete dissolution of wood lignin at less than 80°C for 20 min using an easily recyclable hydrotrope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
256
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(266 citation statements)
references
References 38 publications
5
256
0
Order By: Relevance
“…However, in the process of improving the accessibility of cellulose in the pretreated substrate to enzyme, the energies consumed by these pretreatments are quite high (e.g., pretreatment temperature usually up to 150-220 • C) [7]. In order to improve the removal efficiency of non-cellulosic components with low energy consumption, some new solvents (e.g., deep eutectic solvents (DESs) [8] and hydrotropes [9]) derived pretreatments have been recently reported. For example, hydrotropes have hydrophobic and hydrophilic fractions in their molecular structures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the process of improving the accessibility of cellulose in the pretreated substrate to enzyme, the energies consumed by these pretreatments are quite high (e.g., pretreatment temperature usually up to 150-220 • C) [7]. In order to improve the removal efficiency of non-cellulosic components with low energy consumption, some new solvents (e.g., deep eutectic solvents (DESs) [8] and hydrotropes [9]) derived pretreatments have been recently reported. For example, hydrotropes have hydrophobic and hydrophilic fractions in their molecular structures.…”
Section: Introductionmentioning
confidence: 99%
“…Above the MHC, the hydrotropes can aggregate with the hydrotropic solute to form a water-soluble complex, resulting in higher aqueous solubility of hydrotropic solute [11]. Rencently, Zhu's group reported a MHC of p-toluenesulfonic acid for lignin from poplar wood was 11.5 wt % in water [9]. Under same pretreatment temperature and time, they found that lignin removal was increased with the increase of p-toluenesulfonic acid concentration in water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the carbohydrate fractions of biomass would be affected by catalysts during native lignin degradation. Therefore, removing lignin at the beginning of the biorefinery process is not only a usually applied strategy to facilitate carbohydrate valorization, but also an integrated process for the utilization of fermentable glucose and lignin simultaneously [21]. However, the new C-C bonds would emerge during the process of separating these components, which has an inhibiting effect on depolymerizing under hydrogenolysis conditions due to the higher bond dissociation energies [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The production of second-generation biofuels from lignocellulosic sourcesi samajor concern for industry and academia from at echnology-development perspective. [8][9][10][11][12] In the recent past, severalp retreatment methods have been reported for biomass using steam explosion, [13] such as the sulfite pretreatment to overcome recalcitranceo fl ignocelluloses (SPORL) process, [14] hydrotropes, [15] hot-compressed water pretreatment, [16] dilute acid, [17] inorganic salt, [18] and lime, [19] to remove or alter lignin and hemicellulose and to improvet he enzymatic accessibility of the substrate. The polysaccharides present in wood, which is ad ominant lignocellulosicb iomass, depolymerize upon mild enzymatic hydrolysis or acid hydrolysis to produce the corresponding monosaccharides such as glucose, xylose,a nd mannose.…”
mentioning
confidence: 99%